TINDAK TUTUR EKSPRESIF MENGKRITIK DALAM FILM GILA LU NDRO! DAN IMPLIKASINYA TERHADAP PEMBELAJARAN TEKS ANEKDOT KELAS X SMA - Lia Aprilia; Any Budiarti; Desti Fatin Fauziyyah (STKIP Subang, 2023)
This research aims to describe the expressive speech acts of criticizing in the movie Gila Lu Ndro! and its implication to the learning of anecdote text in class X SMA. The method used in this research is descriptive qualitative research method. The data source in this research is Gila Lu Ndro! movie. The data in this research are the utterances and their contexts that contain expressive speech acts of criticizing contained in the film Gila Lu Ndro. Data collection techniques in this research are listening, free-flowing and note-taking techniques. From this analysis, three things can be concluded: First, direct criticizing speech acts contained in the movie Gila Lu Ndro! are found as many as 20 utterances with several strategies, namely negative assessment as many as 9 utterances, defamation as many as 8 utterances, expression of opposition as many as 2 utterances, and problem statement as many as 1 utterance. Second, indirect criticizing speech acts contained in the movie Gila Lu Ndro! are found as many as 10 speech acts with several strategies, namely correction as much as 1 speech act, speech act for change 1 speech act, advice for change 3 speech acts, suggestion for change 2 speech acts, request for change 1 speech act, expression of uncertainty 1 speech act, and other instructions 1 speech act. Third, the implication of this research on the learning of anecdote text in class X SMA in KD 3.5 evaluates anecdote text from the aspect of implied meaning.